2014
DOI: 10.1007/s11695-014-1491-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Electrical Stimulation Optimized to Inhibit Gastric Motility Reduces Food Intake in Dogs

Abstract: GES with appropriate parameters inhibits gastric motility, and the effects are reproducible. The GES method optimized to inhibit gastric motility reduces food intake in healthy dogs and may have a therapeutic potential for treating obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Gastric stimulation protocols have also been applied to treat obesity by reducing motility, delaying emptying and increasing satiety. Pre-clinical trials showed that stimulation was able to delay gastric emptying, distention, and reduce food intake and eventually led to weight loss (Song et al, 2015). Initial trials in humans showed encouraging results Bohdjalian et al, 2006), but randomized trials have failed to show clinical benefit over a prolonged period (Shikora et al, 2009;Paulus et al, 2020).…”
Section: Gastric Stimulationmentioning
confidence: 99%
“…Gastric stimulation protocols have also been applied to treat obesity by reducing motility, delaying emptying and increasing satiety. Pre-clinical trials showed that stimulation was able to delay gastric emptying, distention, and reduce food intake and eventually led to weight loss (Song et al, 2015). Initial trials in humans showed encouraging results Bohdjalian et al, 2006), but randomized trials have failed to show clinical benefit over a prolonged period (Shikora et al, 2009;Paulus et al, 2020).…”
Section: Gastric Stimulationmentioning
confidence: 99%
“…Basic laboratory research demonstrated that the failure of IGS in producing sufficient weight loss was attributed to its limited effects on the central satiety system and lack of effects on gastric motility, resulting from the use of narrow pulses (40). Most recent studies on GES with wide pulses designed to inhibit gastric motility has shown robust and significant effects on food intake and weight loss in both rats and dogs (41,42). Clinical studies are needed to prove the therapeutic potential of this method for treating obesity.…”
Section: Gastric Electrical Stimulation For Obesitymentioning
confidence: 99%
“…Various types of GES techniques have been studied over the past few decades in animals and humans 12,16 . Recently, inhibitory GES, that impairs gastric motility using trains of pulses with a width longer than 1 ms, has been considered the most promising method for inducing weight loss 16,18–20 . In rats and dogs, the pulse width was proven to be a key parameter related to gastric emptying, and hormonal and neural alterations, leading to a decrease in food intake 21–26 …”
Section: Introductionmentioning
confidence: 99%
“…Adapting the stimulation energy for each individual also appears to be a prerequisite for optimization of GES therapy 12,16,19,20,27 . In addition, for mid‐to‐long‐term therapy efficacy, habituation to GES (i.e., decrease in the response to stimulation over time) must be considered, as reported in dogs 19 and assumed in humans 27 .…”
Section: Introductionmentioning
confidence: 99%